Complete mitochondrial genome of Acrossocheilus yunnanensis (Cypriniformes, Barbinae, Acrossocheilus). (3rd July 2016) - Wu, Jiayun; Huang, Shiqi; Du, Zongjun; Xie, Meng; Zhu, Guangxiang; Wang, Qin; Jiang, Yanzhi; He, Tao; Ren, Hongmei; Zhang, Yi; Wen, Anxiang
Abstract: In this paper, the complete mitochondrial DNA sequence of Acrossocheilus yunnanensis collected from the Qingyi River is determined. The complete mitochondrial genome of A. yunnanensis is a circular molecule of 16, 596 bp in length, and all genes showed the typical gene arrangement conforming to the vertebrate consensus. The 13 protein-coding genes of A. yunnanensis and other 21 Barbinae species from 3 genera were used for phylogenetic analysis using Bayesian inference and maximum likelihood methods. The topology demonstrated the genus Acrossocheilus is relatively close to the Labeo than Garra, the A. yunnanensis may have a common ancestor with A. monticola, where both belong to the non-barred group .